CCITIES AND ENERGY: CONTEMPORARY CHALLENGES: EDITORIAL - Carniatto, Irene; VASCONCELOS, Ana Maria Martins Alves (International Journal of Environmental Resilience Research and Science, 2021)
The phenomenon of metropolization (urban occupation that goes beyond the limits of cities) is a result of an intense urbanization process in Brazil, which led to the development of large metropolitan in Brazil, the centers such as São Paulo, Rio de Janeiro, Porto Alegre, Curitiba, Campinas, Manaus, and others. This scenario has impacted directly on levels increase of greenhouse gases, emitted by anthropogenic activities. The representative authorities got together “almost 200 countries to obtain effective actions to reduce pollutant gas emissions” (Agência Câmara de Notícias, 2021). We present a unique volume, coordinated by the researchers, Dr. Ricardo Morel Hartmann (from the Latin American University – UNILA) and Dr. Acires Dias (Federal University of Santa Catarina – UFSC). It presents research that analyzed the exergetic efficiency of important cities such as: Recife, Brazil, which presented an efficiency of 22.58%; Mexico City, Mexico (22.16%); Lima, Peru (20.9%); Santos, São Paulo, Brazil (19.70%); and Buenos Aires, Argentina (14.9%).